Roadmap for Equality in Education: Problems, Solutions and Implementation Strategies - Yıldırımer, Kürşat Şahin (Dinamika Ilmu, 2024)
Equality in education is a fundamental goal for societies, and educational systems need to provide equal opportunities for all individuals to realize their potential. However, in the current situation, economic, social and cultural differences create inequality of opportunity in education and this is a fundamental problem of education systems. This article emphasizes the importance of achieving the goal of equality in education and discusses the problems encountered in achieving this goal. By examining the root causes and consequences of inequalities in education, it aims to better understand these problems. Furthermore, the article presents key strategies for achieving equity in education. These strategies include reviewing education policies, training and supporting teachers, increasing access to education for disadvantaged groups, using technology-based education methods and developing anti-discrimination awareness programs. In this context, the goal of achieving equity in education is critical for social development and human rights, and the paper aims to provide a roadmap for equity in education, presenting the steps and strategies needed to achieve this important goal.